Detection of acute stroke with diffusion-weighted MRI. - Dunithan AJM; Cox LA; Long BW (Radiologic Technology)
Diffusion-weighted MRI is a new imaging method that can detect acute ischemic stroke within an hour of onset. The first hour following a stroke is crucial, because it is during this time that damaged tissue can be saved. Diffusion-weighted imaging measures the water mobility in tissue. Using these measurements, MRI images can be reconstructed to provide quantified data regarding actual tissue damage. The initial images are obtained using a modified fast spin echo, gradient echo sequence, echo-planar imaging or a navigator echo. These ultrafast sequences are used to eliminate motion artifacts so maximum data can be obtained.